PERUBAHAN STRUKTUR SOSIAL MASYARAKAT PETANI DI KELURAHAN MANCASAN KECAMATAN BAKI KABUPATEN SUKOHARJO - Pamungkas, Muhamad Ichsan Tri; Danang Purwanto; Dwi Astutik (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This research focuses on the problem of social change that occurs among farming communities in Mancasan Village. There has been a shift in the structure of the farming community from society's point of view which has caused a decline in the interest of the younger generation to be interested in the farming profession at this time. The aim of this research is to find out the causes of the phenomenon of social structural change that occurs among the farming community in Mancasan Village and the impacts caused by this phenomenon of social change. The method used in this research is descriptive qualitative which aims to describe various phenomena, situations and conditions of social reality in society. Information was collected through interviews with a number of informants and observations in the field. The research results show that social change occurs because of the low level of welfare within society regarding the farming profession which has an impact on the process of changing the interest of the younger generation in the farming profession. These changes cannot be separated from the impact of developments in science and technology. The changes that occur bring various impacts, both positive and negative.